Comparação da eficiência dos caldos de enriquecimento seletivo no isolamento de Salmonella Dublin - Silva, D. G. [UNESP]; Fagliari, J. J. [UNESP]; Garcia, T. B. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
The aim of this study was to compare three different selective enrichment broths: Rappaport-Vassiliadis (RV), selenite cystine (SC) and Muller-Kauffmann tetrathionate (MKT) for Salmonella Dublin isolation from faecal samples of calf experimentally infected. The bacteriological procedure involved pre-enrichment stages in Hajna-GN broth (only for the samples inoculated in RV broth), selective enrichment, culture in modified brilliant green agar (BGA), presumptive biochemistry tests (using triple-sugar-iron agar and lysine-agar) and slide agglutination test with poli-O and poli-H Salmonella antiserum. The effects of enrichment temperatures using RV broth were also evaluated (37ºC and 42ºC). SC broth was significantly more efficient in the isolation of Salmonella Dublin (P<0,05), whereas RV broth incubated at 42ºC had a lower efficiency in the microbiological isolation.
Comparison of the efficiency of selective enrichment broths for Salmonella Dublin isolation
Keywords: Salmonella Dublin; selective enrichment; Calves; feces; Bezerro; Salmonella Dublin; meio seletivo; Fezes